Effects of the Btk-Inhibitors Remibrutinib (LOU064) and Rilzabrutinib (PRN1008) With Varying Btk Selectivity Over Tec on Platelet Aggregation and in vitro Bleeding Time - Duan, Rundan; Goldmann, Luise; Brandl, Richard; Spannagl, Michael; Weber, Christian; Siess, Wolfgang; von Hundelshausen, Philipp (Frontiers in Cardiovascular Medicine, 2021)
Background: Bruton tyrosine kinase inhibitors (BTKi) are used in B-cell malignancies and in development against various autoimmune diseases. Since Btk is also involved in specific pathways of platelet activation, BTKi might be considered to target platelet GPVI/GPIb-mediated atherothrombosis and platelet FcγRIIA-dependent immune disorders. However, BTKi treatment of patients with B-cell malignancies is frequently associated with mild bleeding events caused possibly by off-target inhibition of Tec. Here, we compared the platelet effects of two novel BTKi that exhibit a high (remibrutinib) or low (rilzabrutinib) selectivity for Btk over Tec. Methods and Results: Remibrutinib and rilzabrutinib were pre-incubated with anticoagulated blood. Platelet aggregation and in vitro bleeding time (closure time) were studied by multiple electrode aggregometry (MEA) and platelet-function analyzer-200 (PFA-200), respectively. Both BTKi inhibited atherosclerotic plaque-stimulated GPVI-mediated platelet aggregation, remibrutinib being more potent (IC50 = 0.03 μM) than rilzabrutinib (IC50 = 0.16 μM). Concentrations of remibrutinib (0.1 μM) and rilzabrutinib (0.5 μM), >80% inhibitory for plaque-induced aggregation, also significantly suppressed (>90%) the Btk-dependent pathways of platelet aggregation upon GPVI, von Willebrand factor/GPIb and FcγRIIA activation stimulated by low collagen concentrations, ristocetin and antibody cross-linking, respectively. Both BTKi did not inhibit aggregation stimulated by ADP, TRAP-6 or arachidonic acid. Remibrutinib (0.1 μM) only slightly prolonged closure time and significantly less than rilzabrutinib (0.5 μM). Conclusion: Remibrutinib and rilzabrutinib inhibit Btk-dependent pathways of platelet aggregation upon GPVI, VWF/GPIb, and FcγRIIA activation. Remibrutinib being more potent and showing a better profile of inhibition of Btk-dependent platelet activation vs. hemostatic impairment than rilzabrutinib may be considered for further development as an antiplatelet drug.